Pharmaceutical evaluation of different shampoo brands in local Saudi market - Bushra T. AlQuadeib; Eram K.D. Eltahir; Rana A. Banafa; Lama A. Al-Hadhairi (Elsevier, 2018)
Shampooing is the most common form of hair treatment. Shampoos are primarily products aimed at cleansing the hair and scalp. There are many brands of shampoos in Saudi Arabia, available from different sources, locally and imported from other countries. This study aims to investigate whether such brands comply with the Saudi standard specifications for shampoos, issued by the National Center for Specifications and Standards, and to what extent these specifications are applied. Six shampoo brands were randomly collected from Riyadh market (Pantene®, Sunsilk®, Herbal essences®, Garnier Ultra Doux®, Syoss® and L'Oreal Elvive®). The selected shampoos were evaluated according to their physicochemical properties, including organoleptic characterization, pH measurement, percentage of solid content, rheological measurements, dirt dispersion level, foaming ability and foam stability, and surface tension. All shampoos had a good percentage of solids, excellent foam formation with stable foam and a highly viscous nature. Regarding the pH measurement, all shampoo samples were within the specified range with good wetting ability. Keywords: Shampoo, Physicochemical approach, Evaluation